Operationalising flexible planning coupled with ongoing assessment strategies. A pragmatic, longitudinal randomized study in U13 female volleyball team - Loureiro, M.; Mesquita, I.; Ramos, A.; Coutinho, P.; Ribeiro, J.; Clemente, F. M.; Nakamura, F. Y.; Afonso, J. (International Journal of Sports Science and Coaching, 2024)
Embracing a tailor-made approach to training, the aim of this study was to understand how ongoing adaptation and planning of training sessions (through bidirectional feedback between planning and assessment) contrasts with a more rigid planning with only 4-weeks adaptations, and how those differences impact on learning trajectories. A longitudinal, randomized design with a qualitative analysis was conducted during a full season with 24 girls from a U-13 volleyball team: an experimental group (E.G.) had daily adjusted planning and a contrast group (C.G.) had 4-weeks adjusted planning. Data analysis considered reflective diaries, field notes, video analysis and ongoing assessments using Game Performance Assessment Instrument, to gain a deeper understanding of athletes` progression and identify their struggles. Based on ongoing and punctual assessment (through GPAI) the planning of the two groups diverged significantly in content and drill structure. Ongoing assessment allowed to solve, in E.G., unpredictable issues as well as develop flexible planning to adapt the specific drills and re-adapt the content. Those adaptations occurred in many ways such as: type of the drill, setting goals and changing the content of the session. In C.G., 4 weeks adaptations were permitted to moderate the extending disparities between rigid planning and ongoing adaptations, aiming to balance the group's levels. Our findings highlighted the importance of bidirectional feedback between assessment and planning, informing the coaches to possible adaptation of the training. Given the differences in learning rates, unforeseen circumstances and players` characteristics, flexible planning and assessment is paramount to effectively steer the learning process.